2019
DOI: 10.3390/agriculture9020038
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cultivated Area, Field Boundary and Overlapping for A Plowing Operation Using ISO 11783 Communication and D-GNSS Position Data

Abstract: Easily available and detailed area-related information is very valuable for the optimization of crop production processes in terms of, e.g., documentation and invoicing or detection of inefficiencies. The present study dealt with the development of algorithms to gain sophisticated information about different area-related parameters in a preferably automated way. Rear hitch position and wheel-based machine speed were recorded from ISO 11783 communication data during plowing with a mounted reversible moldboard p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Currently, these data are combined with GNSS sensors for site specific management practices, and also due to their reduced price this allows archiving data and operations with position references. The article by Heiß et al [24] is titled "Determination of Cultivated Area, Field Boundary and Overlapping for A Plowing Operation Using ISO 11783 Communication and D-GNSS Position Data". In this study, authors developed an algorithm that deals with georeferenced data recorded during plowing operation in order to calculate different area-related parameters in an automated way.…”
Section: Plowing Operation Archived Datamentioning
confidence: 99%
“…Currently, these data are combined with GNSS sensors for site specific management practices, and also due to their reduced price this allows archiving data and operations with position references. The article by Heiß et al [24] is titled "Determination of Cultivated Area, Field Boundary and Overlapping for A Plowing Operation Using ISO 11783 Communication and D-GNSS Position Data". In this study, authors developed an algorithm that deals with georeferenced data recorded during plowing operation in order to calculate different area-related parameters in an automated way.…”
Section: Plowing Operation Archived Datamentioning
confidence: 99%
“…Commercial loggers, backed by their powerful software suites, are favorable choices among researchers for capturing CAN data via the ISOBUS diagnostic port for machine-centric analysis. For instance, a commercial logger was configured in [ 25 ] to log GNSS data, to determine field boundaries for plowing operations. Moreover, three commercial loggers were evaluated in [ 26 ] for their feasibilities in real-time engine speed and load analysis.…”
Section: Related Workmentioning
confidence: 99%
“…A large number of tests showed that the tillage depth could reach more than 15 cm and the burying rate of stubbles was 90%, which met the requirements of the agricultural machinery standard (NY/T499-2013) for rotary tillers (the tillage depth should be greater than 12 cm and the burying rate should be greater than 80%). In light of the complex surface environment in the field, researchers have mainly used inclination sensors [8][9][10], lasers [11][12][13][14], and the global positioning and navigation system (GNSS) [15][16][17][18] to develop measurement methods of field surface data. The inclination sensor can estimate the height change of the field surface through the pitch angle of the vehicle, which is low in cost and easy to develop.…”
Section: Introductionmentioning
confidence: 99%